ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN DENGAN MENGGUNAKAN IMPORTANCE PERFORMANCE ANALYSIS PADA KONSUMEN LAPTOP ASUS DI SEMARANG - Aldila Garinapuri, Pangrae; Sugiarto, Yohanes (Faculty of Economics and Business Diponegoro University, 2015)
This study aims to examine the factors - factors that influence purchasing decisions Asus laptop in Semarang. These data were collected from 100 consumers or users Asus laptop.The samples in this study using simple random sampling. The analysis used in this study include the validity and reliability testing and Importance Performance Analysis (IPA).The results of the analysis using Importance Performance Analysis (IPA) to determine the level of consumer expectation gap between the amount of product performance. Based on data analysis of each - each purchase decision factors experienced negative gap (-), where the factor of product quality experience gap -0.65. Factor Price happen gap -0.55. Promotion factor -0.86. and the after-sales service factor -0.77. Where the expectation is greater than the performance of the products that can be used as a reference diharapkan.Hal to improve product performance